Pooled Population Pharmacokinetic Analyses of Venetoclax in Patients Across Indications and Healthy Subjects from Phase 1, 2, and 3 Clinical Trials. - Gong, Jingqi Q. X.; Suleiman, Ahmed A.; Menon, Rajeev; Deng, Rong; Mensing, Sven; Salem, Ahmed Hamed (Journal of Clinical Pharmacology, 2023)
Following the decade‐long clinical investigation, venetoclax has accrued pharmacokinetic (PK) data across multiple populations and widely ranging demographics, intrinsic, and extrinsic factors. We leveraged these rich data to systematically characterize venetoclax PK and assess covariate effects with population PK modeling. Plasma concentration–time data were pooled from 3016 subjects enrolled in 41 phase 1, 2, and 3 clinical studies, including patients from 9 indications and healthy volunteers. A nonlinear mixed‐effect model was developed. Covariates were evaluated with full covariate modeling approach. A 2‐compartment model with 3 transit absorption compartments described the data well. The impact of moderate and strong cytochrome P450 (CYP) 3A inhibition on apparent clearance (CL/F), female sex on apparent volume of distribution, food effect on relative bioavailability, and dose nonlinearity was confirmed. Newly identified covariate effects include 48% lower CL/F in subjects with severe hepatic impairment, 61% higher bioavailability in Asian subjects. When multiple CYP3A inhibitors are taken simultaneously, a 49% decrease in CL/F was estimated with multiple moderate inhibitors, more substantial than the 22% decrease of a single moderate inhibitor. An 85% decrease in CL/F was indicated when at least 1 strong CYP3A inhibitor was taken in combination, comparable to that of a single strong inhibitor. A venetoclax cross‐indication population PK model with improved absorption‐phase characterization was developed. Covariate analyses suggested lower CL/F for subjects with severe hepatic impairment and higher bioavailability in Asian subjects. Further decrease in CL/F was indicated when multiple moderate CYP3A inhibitors are present, compared to a single moderate inhibitor.